2019
DOI: 10.1021/acscatal.8b03965
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Interaction between Palladium and N-Doped Carbon Nanotubes: Effect of Electronic Property on Activity for Nitrobenzene Hydrogenation

Abstract: Nitrogen dopants of carbon materials remarkably improve the stability and tune the catalytic performance of supported metal nanoparticles. However, it is still controversial how the Pd−N metal−support-interaction (MSI) influences the catalysis. Herein, the density function theory (DFT) calculations and X-ray photoelectron spectroscopy (XPS) were combined to rationalize the Pd−N MSI. DFT calculations suggested that Pd adsorbs on N-doped carbon nanotubes (N@CNTs) and donates electrons to pyridinic nitrogen. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 56 publications
4
81
0
4
Order By: Relevance
“…56 Compared with the PdAu/CB sample (Fig. S1 †), the Pd and Au peak positions of PdAu/NCB shi to higher binding energies, which is attributed to the metal-support interaction (MSI) between PdAu nanoparticles and NCB, 57 suggesting an enhanced attraction force between the PdAu atoms and the NCB support. 48…”
Section: Morphology and Structurementioning
confidence: 98%
See 1 more Smart Citation
“…56 Compared with the PdAu/CB sample (Fig. S1 †), the Pd and Au peak positions of PdAu/NCB shi to higher binding energies, which is attributed to the metal-support interaction (MSI) between PdAu nanoparticles and NCB, 57 suggesting an enhanced attraction force between the PdAu atoms and the NCB support. 48…”
Section: Morphology and Structurementioning
confidence: 98%
“…Obviously, N-doping can improve the catalytic performance due to an enhanced attraction force between PdAu atoms and the NCB support. 48,57 We also investigate the effect of temperature on the hydrogenation reaction. Four different temperatures ranging from 20 to 35 C were chosen for the reduction of 2-NP, 3-NP and 4-NP.…”
Section: Hydrogenation Of Nitrophenolsmentioning
confidence: 99%
“…It is widely accepted that the nitrogen atoms in metal modified N ‐doping carbon catalysts act as base sites which could increase the performance of various reactions such C−C bond formation, C−O bond formation, reduction, oxidation, C−H activation, etc . Recently, it is observed that the adsorption of Pd on pyridinic‐ N is more favorable than that on graphitic‐ N . Here, we tried to synthesize pyridinic‐ N doped carbon support by keeping low temperature for doping so that only one type i. e .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Previous investigations suggest that amino acid residues around the catalytic active sites of enzymes could assist enriching,organizing, and activating substrates via non-covalent interactions. [4][5][6][7][8] Generally, the catalytic performance of metal NPs can be modulated by modifying its physicochemical properties,s uch as the size, shape,a nd interactions with supports. [4][5][6][7][8] Generally, the catalytic performance of metal NPs can be modulated by modifying its physicochemical properties,s uch as the size, shape,a nd interactions with supports.…”
mentioning
confidence: 99%
“…[3] Supported metal nanoparticles are an important class of catalyst materials and they have been widely used in industry for various chemical reactions,s uch as hydrogenation, oxidation, C À Cc oupling,a nd isomerization. [4][5][6][7][8] Generally, the catalytic performance of metal NPs can be modulated by modifying its physicochemical properties,s uch as the size, shape,a nd interactions with supports. [4] Additionally,p revious investigations have showcased the importance of microenvironments in tuning the catalytic performance of metal NPs by affecting its adsorption energy and adsorption modes of substrates, [9][10][11][12][13] which could be realized via the generating as teric hindrance around metal NPs, [14][15][16][17] introducing the binding site with specific functional group near metal NPs, [18][19][20][21] and so on.Thec atalytic hydrogenation of benzoic acid (BA) is of pivotal importance in industry.H owever,n egligible conversion of BA was obtained in aprotic organic solvents under similar conditions (60 8 8C, 1MPa) over metal NPs.…”
mentioning
confidence: 99%